Odù Ifá in Transition: Contemplating Boundary Mechanisms in Discursive and Critical Appreciation of the Ifá Corpus - Anọ́ba, Ibrahim B. (Journal of religion in Africa, 2022)
Some Ifá priests and scholars have argued that noninitiates should not engage the Odù Ifá corpus. They suggest that such an undertaking could be spiritually dangerous and lead to the corruption of Ifá’s messages that its practitioners have established. This article demonstrates why the Odù Ifá corpus should be open to engagement by noninitiates who are familiar with Òrìṣà logics and the intricacies of the Yorùbá language in purely academic and nonspiritual spaces. Its method is premised on reviewing a particular category of literature on Yorùbá religion, and examining the corpus as an intellectual tradition within the web of cultural globalization.